Analysis of Cavernous Malformations: Experience with 18 Cases - Haciyakupoglu, Ersin; Yilmaz, Dervis Mansuri; Kinali, Burak; Akbas, Tugana; Haciyakupoglu, Sebahattin (TURKISH NEUROSURGICAL SOC, 2019)
AIM: To analyze the results of stereotactic radiosurgery (SRS) or surgical treatment of 18 cases with cavernous malformation and report 2 cases with unusual localization and size. MATERIAL and METHODS: We present 11 and 8 patients who underwent surgery and SRS between 2010 and 2018 respectively. The operated group comprised six men and five women (mean age, 33.6 years). SRS was performed in five men and three women (mean age, 33.3 years). All patients were diagnosed and followed-up with magnetic resonance imaging. Stereotactic navigation was not used for lesion localization. The lesion, including the area with hemosiderin, was easily excised using microsurgical approach. RESULTS: Except for recurrent headache, all symptoms of patients who underwent surgery resolved rapidly. Hemorrhage developed in two of our patients after SRS. One of them refused to undergo surgery and recovered completely with steroid therapy, whereas the other underwent surgery after detection of cavernous malformation at the posterior fossa, with a dimension of 26.8x26.2 mm and occluding the fourth ventricle. CONCLUSION: In patients without significant preoperative morbidity risk, surgical excision is the gold standard of treatment. SRS is performed in surgically inaccessible, deeply located, multiple cavernous malformations in the brain stem and eloquent area. Of note, giant aneurysm is defined as an aneurysm with a diameter of at least 25 mm

however, there is no dimension threshold defined for giant CM, and the size of giant aneurysm can be accepted as a valid criterion for giant CM. Our 2 cases had giant CM and up to our knowledge the case with giant CM at the posterior fossa is the first giant CM at the posterior fossa in the English literature.
Keywords: Cavernous malformation; Giant cavernous malformation; Stereotactic radiosurgery